1996
DOI: 10.1080/03014223.1996.9518090
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate bait preferences of wasps (Vespula vulgarisandV. germanica) (Hymenoptera: Vespidae) in New Zealand

Abstract: Carbohydrates are both a source of food and a potential bait for control of common and German wasps. Carbohydrate preferences of wasps were determined in a series of paired trials by counting the number of wasps caught in traps baited with carbohydrate-based baits versus a standard proteinbased bait. Factors influencing wasp attraction to carbohydrate-based baits included bait type, season, weather, and location. A 30% sucrose solution was more attractive than honey, jams, gels, or dry (solid) sugars. The sucr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…The addition of chemicals (AAIB) caused less honeybee captures when mixed with the sugary food bait (again, just the opposite of yellowjacket captures) maybe because the chemicals acted as a repellent mixture, or because they affected the olfactory receptors or disrupted foraging A. mellifera before they reached the trap. Similar results have been published by Spurr (1996), who found that carbohydrates (including jam and condensed milk but not mixed with AAIB) were highly attractive for A. mellifera. These results may have been influenced by the vicinity of two apiaries.…”
Section: Resultssupporting
confidence: 79%
“…The addition of chemicals (AAIB) caused less honeybee captures when mixed with the sugary food bait (again, just the opposite of yellowjacket captures) maybe because the chemicals acted as a repellent mixture, or because they affected the olfactory receptors or disrupted foraging A. mellifera before they reached the trap. Similar results have been published by Spurr (1996), who found that carbohydrates (including jam and condensed milk but not mixed with AAIB) were highly attractive for A. mellifera. These results may have been influenced by the vicinity of two apiaries.…”
Section: Resultssupporting
confidence: 79%
“…Management strategies for pestiferous social wasps have focused on poison baits to reduce or eliminate wasps and their nests, and on chemical or food attractants to trap foraging workers or queens . Combinations of pesticides and meats have been used to control the western yellowjacket, Vespula pensylvanica (Saussure), the common yellowjacket, V. vulgaris (L.), and the German yellowjacket, V. germanica (F.) . Although protein‐based poison baits have shown efficacy, they are not extensively used because of their expense, their short‐term attractiveness and various adverse effects on non‐target species and the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Mitigation of social wasp numbers and pest status can sometimes be achieved with poison baits (Chang 1988;Hanna et al 2012) or lures for traps that are based on food materials (Dvorak & Landolt 2006;Ross et al 1984;Silveira et al 2005;Spurr 1995Spurr , 1996 or chemical attractants (Davis et al 1969(Davis et al , 1973Landolt 1998). However, there are no demonstrated food baits or chemical attractants that might be used to trap most paper wasps.…”
Section: Introductionmentioning
confidence: 98%